ANALISIS KUALITAS PELAYANAN DAN KINERJA PEGAWAI KANTOR DESA AMBULU KECAMATAN SUMBERASIH KABUPATEN PROBOLINGGO TERHADAP KEPUASAN MASYARAKAT - Husni Mubaroq; Yulia Nurul Hidayati (Universitas Bina Taruna Gorontalo, 2022)
This study aims to determine and describe the quality of service and employee performance on community satisfaction in Ambulu Village, Sumberasih District, Probolinggo Regency. This study uses descriptive quantitative methods by setting a sample of 100 people with the aim of explaining the relationship between variables through the submission of formulated hypotheses. The data analysis technique applied is multiple regression analysis. The results of the analysis answered that the quality of service and employee performance to the community there was a significant relationship. The level of significance of service quality and employee performance on employee performance can be seen through the results of the F test, it is found that service quality and employee performance simultaneously affect community satisfaction. This is evidenced by the statement, if F count F table or significant value <0.05. Then, the result of F Count is greater than F table which is 35.957 > 2.75 then Ha is accepted, which means that service quality and employee performance simultaneously have an effect on community satisfaction in Ambulu village, Sumberasih sub-district, Probolinggo district.